Environmental degradation of polymer nanocomposites - Afdhal, Junaidi; Ahmad Fauzi, Ismail; Norazlianie, Sazali (Woodhead Publishing, 2026)
Polymer nanocomposites have become essential in various industries due to their impressive mechanical strength, thermal stability, and electrical properties. These materials, which integrate nanoscale fillers into polymer matrices, offer enhanced properties like reduced weight and increased durability, surpassing traditional composites. However, the high performance observed in controlled environments does not always translate to real-world conditions, where a variety of environmental factors can lead to degradation. Understanding how these factors—such as ultraviolet (UV) radiation, thermal cycling, humidity, chemical exposure, and biological activity—affect polymer nanocomposites is crucial for their reliable use in practical applications. This chapter focuses on the combined effects of environmental factors on polymer nanocomposites, exploring both synergistic interactions that intensify degradation and antagonistic interactions that may mitigate these effects. By analyzing case studies, characterization techniques, and strategies for enhancing environmental stability, this chapter aims to equip researchers and engineers with the knowledge needed to improve the durability and performance of these advanced materials in various applications.